Management of cardiac sarcoidosis - Sharma, Rakesh; Kouranos, Vasileios; Cooper, Leslie T; Metra, Marco; Ristic, Arsen; Heidecker, Bettina; Baksi, John; Wicks, Eleanor; Merino, Jose L; Klingel, Karin; Imazio, Massimo; de Chillou, Christian; et al. (European heart journal, 2024)
Cardiac sarcoidosis (CS) is a form of inflammatory cardiomyopathy associated with significant clinical complications such as high-degree atrioventricular block, ventricular tachycardia, and heart failure as well as sudden cardiac death. It is therefore important to provide an expert consensus statement summarizing the role of different available diagnostic tools and emphasizing the importance of a multidisciplinary approach. By integrating clinical information and the results of diagnostic tests, an accurate, validated, and timely diagnosis can be made, while alternative diagnoses can be reasonably excluded. This clinical expert consensus statement reviews the evidence on the management of different CS manifestations and provides advice to practicing clinicians in the field on the role of immunosuppression and the treatment of cardiac complications based on limited published data and the experience of international CS experts. The monitoring and risk stratification of patients with CS is also covered, while controversies and future research needs are explored.
Keywords: Cardiomyopathies; Epidemiology; Diagnosis; lidé; náhlá srdeční smrt; kardiomyopatie; Sarcoidosis; Immunosuppression; Immunosuppressive Agents; Management; Multidisciplinary; sarkoidóza; Screening; imunosupresiva; Death, Sudden, Cardiac; Cardiac sarcoidosis; Humans